Β-Cyclodextrin as a supramolecular catalyst for the synthesis of dihydropyrano[2, 3-c]pyrazole and spiro[indoline-3, 4′-pyrano[2, 3-c]pyrazole] in aqueous medium. Issue 19 (6th May 2015) - Tayade, Yogesh A.; Padvi, Swapnil A.; Wagh, Yogesh B.; Dalal, Dipak S.
Graphical abstract: Abstract: Supramolecular β-cyclodextrin (β-CD) as a highly efficient, biodegradable, and reusable catalyst for the synthesis of pyranopyrazole derivatives is investigated via a one-pot four component reaction of aldehydes and isatins, hydrazine hydrate, malononitrile, and β-keto ester in H2 O–EtOH (9:1) at 80 °C for first time under neutral conditions.